Comparative analysis of alternative fuels in detonation combustion - Azami, M. H.; Savill, Mark A. (AIAA, 2016)
Detonation combustion prominently exhibits high thermodynamic efficiency which leads to better performance. As compared to the conventionally used isobaric heat addition in a Brayton cycle combustor, detonation uses a novel isochoric Humphrey cycle which utilises shocks and detonation waves to provide pressure-rise combustion. Such unsteady combustion has already been explored in wave rotor, pulse detonation engine and rotating detonation engine configurations as alternative technologies for the next generation of the aerospace propulsion systems. However, in addition to the better performance that the detonation mode of combustion offers, it is crucial to observe the environmental concerns as well. Therefore, this paper presents a one-dimensional numerical analysis for alternative fuels: Jet-A, Acetylene, Jatropha Bio-synthetic Paraffinic Kerosene, Camelina Bio-synthetic Paraffinic Kerosene, Algae Biofuel, and Microalgae Biofuel under detonation combustion conditions. For simplicity, the analysis is modelled using an open tube geometry. The analysis employs the Rankine-Hugoniot Equation, Rayleigh Line Equation, and Zel’dovich–von Neumann–Doering model and takes into account species mole, mass fraction, and enthalpies-of-formation of the reactants. Initially, minimum conditions for the detonation of each fuel are determined. Pressure, temperature, and density ratios at each stage of the combustion tube for different types of fuel are then explored systematically. Finally, the influence of different initial conditions is numerically examined to make a comparison for these fuels.